Prognostic value of somatosensory evoked potentials, neuron-specific enolase, and S100 for short-term outcome in ischemic stroke - Haupt, Walter F. (J Neurophysiol, 2015)
To predict short-term outcome in acute ischemic stroke, we analyzed somatosensory evoked potentials (SEP) and biochemical parameters [neuron-specific enolase (NSE) and S100 protein] in a prospective study with serial measurement. In 31 patients with 1st middle cerebral artery infarction, serum NSE and S100 protein were measured daily between days 1 and 6 poststroke. The N20 and N70 components of the SEP (SEP20 and SEP70) were determined on days 1 and 6. SEP and biochemical markers in stroke patients were compared with a control group. Short-term outcome was assessed by the modified Rankin Scale (mRS) at days 7-10 and was dichotomized between good (mRS 0–2) and poor (mRS ≥3) outcome. Specificity and positive predictive value (PPV) were high at day 1 for SEP (SEP20: 100% for both; SEP70: 93 and 88%, respectively) compared with lower values for NSE (67 and 50%) and S100 (23 and 57%). In contrast, S100 showed the highest sensitivity at day 1 with 77% compared with a relatively low sensitivity of NSE (31%) and SEP (SEP20: 35%, SEP70: 47%). The biochemical markers showed an improving sensitivity over time with best values (>90%) between days 3 and 4 at the expense of a lower specificity. Specificity and PPV of SEP on day 6 was still 100% with sensitivity increasing up to 53% (SEP20) and 60% (SEP70). SEP could early differentiate between good and poor outcome and reliably predict poor outcome. Since biochemical markers and SEP complement each other in the prognosis of stroke, a combined application of these markers seems promising.